2021
DOI: 10.1038/s41598-021-82413-y
|View full text |Cite
|
Sign up to set email alerts
|

An under-ice bloom of mixotrophic haptophytes in low nutrient and freshwater-influenced Arctic waters

Abstract: The pelagic spring bloom is essential for Arctic marine food webs, and a crucial driver of carbon transport to the ocean depths. A critical challenge is understanding its timing and magnitude, to predict its changes in coming decades. Spring bloom onset is typically light-limited, beginning when irradiance increases or during ice breakup. Here we report an acute 9-day under-ice algal bloom in nutrient-poor, freshwater-influenced water under 1-m thick sea ice. It was dominated by mixotrophic brackish water hapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…The K d (PAR) for downwelling PAR was 0.25 m −1 with snow and 0.32 m −1 without snow, were also comparable to previous below-ice coefficients in Kangerlussuaq [24]. However, the present coefficients were nearly two times higher than values of 0.15 m −1 in the high Arctic Young Sound [32] and 0.17 m −1 in the central Arctic Ocean [33]. The twofold higher K d (PAR) in Kangerlussuaq is likely related to higher SPM concentrations in Kangerlussuaq where partitioning analyses showed that 72% of PAR attenuation was related to SPM.…”
Section: Spectral Distribution and K D (Par)supporting
confidence: 85%
“…The K d (PAR) for downwelling PAR was 0.25 m −1 with snow and 0.32 m −1 without snow, were also comparable to previous below-ice coefficients in Kangerlussuaq [24]. However, the present coefficients were nearly two times higher than values of 0.15 m −1 in the high Arctic Young Sound [32] and 0.17 m −1 in the central Arctic Ocean [33]. The twofold higher K d (PAR) in Kangerlussuaq is likely related to higher SPM concentrations in Kangerlussuaq where partitioning analyses showed that 72% of PAR attenuation was related to SPM.…”
Section: Spectral Distribution and K D (Par)supporting
confidence: 85%
“…Similar observations in the community structure have recently been made in the Young Sound fjord in Northeast Greenland. Here, a bloom of mixotrophic haptophytes developed in ice covered surface waters during early spring [19]. The two locations differ considerably with regard to salinity and nutrient concentrations.…”
Section: Discussionmentioning
confidence: 95%
“…The periods with ice cover have been declining during the past decades due climate change and this is expected to impact the timing and dynamics of the spring bloom, and the trophic modes of the protist community [13,14]. Phytoplankton blooms have occasionally been found to develop before the sea ice melts [15][16][17], and recent studies have recognized the abundance of parasitic and mixotroph protists in sea ice presence [18,19]. The seeding of the pelagic phototrophic spring bloom event by sea ice algae has also been discussed, especially in relation to multiyear sea ice [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…We further show that within-Arctic HGT, exemplified by genes coding for ice-binding domains, is an important component of this convergent evolution. The overall results position within-ocean HGT as a mechanism of environmental adaptation, which may occur via biotic interactions characteristic of Arctic species such as photo-mixotrophy (McKie-Krisberg & Sanders, 2014; Søgaard et al, 2021) and viral infection (Irwin et al, 2021; Nelson et al, 2021); or even the direct exchange of genetic material through the Arctic water column or sea ice (Raymond, 2011; Raymond & Kim, 2012).…”
Section: Discussionmentioning
confidence: 99%